Goethite Mineral Dissolution to Probe the Chemistry of Radiolytic Water in Liquid-Phase Transmission Electron Microscopy - Couasnon, Thaïs; Fritsch, Birk; Jank, Michael P.M.; Blukis, Roberts; Hutzler, Andreas; Benning, Liane G. (Advanced Science, 2023)
Liquid-Phase Transmission Electron Microscopy (LP-TEM) enables in situ observations of the dynamic behavior of materials in liquids at high spatial and temporal resolution. During LP-TEM, incident electrons decompose water molecules into highly reactive species. Consequently, the chemistry of the irradiated aqueous solution is strongly altered, impacting the reactions to be observed. However, the short lifetime of these reactive species prevent their direct study. Here, the morphological changes of goethite during its dissolution are used as a marker system to evaluate the influence of radiation on the changes in solution chemistry. At low electron flux density, the morphological changes are equivalent to those observed under bulk acidic conditions, but the rate of dissolution is higher. On the contrary, at higher electron fluxes, the morphological evolution does not correspond to a unique acidic dissolution process. Combined with kinetic simulations of the steady state concentrations of generated reactive species in the aqueous medium, the results provide a unique insight into the redox and acidity interplay during radiation induced chemical changes in LP-TEM. The results not only reveal beam-induced radiation chemistry via a nanoparticle indicator, but also open up new perspectives in the study of the dissolution process in industrial or natural settings.
CRIS-Team Scopus Importer:2023-09-15
Keywords: dissolutions; electron beam effects; goethite; liquid-phase transition electron microscopy; water radiolysis